1997
DOI: 10.1021/jp961814y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Thymine on Gold Single-Crystal Electrodes

Abstract: We have examined the adsorption of thymine on (111), (100), and (210) gold single-crystal surfaces. The adsorption behavior on these three surfaces has been investigated by classical electrochemical methods like cyclic voltammetry and capacitance−potential measurements. Additionally in situ scanning tunneling microscopy (STM) and ex situ photoelectron spectroscopy (XPS) measurements have been performed for the adsorption of thymine on the (111) surface. The capacitance measurements as well as cyclic voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
81
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 49 publications
19
81
1
3
Order By: Relevance
“…This discrepancy between the conclusions based on the two techniques might arise from the fact that each of the techniques is sensitive to a different region of the monolayer. Whereas HREELS probes mainly the end of the molecules facing the vacuum, as most processes are region position ss-poly(C) ss-poly(A) ss-poly(T) literature [29][30][31][32][33][34][35] due to impact mechanisms, XPS probes the coverage on the gold itself. It is quite possible that, although the layer is not dense and fully ordered near the substrate, the long molecules arrange themselves in such a way that their tails, facing the vacuum, are well-ordered.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy between the conclusions based on the two techniques might arise from the fact that each of the techniques is sensitive to a different region of the monolayer. Whereas HREELS probes mainly the end of the molecules facing the vacuum, as most processes are region position ss-poly(C) ss-poly(A) ss-poly(T) literature [29][30][31][32][33][34][35] due to impact mechanisms, XPS probes the coverage on the gold itself. It is quite possible that, although the layer is not dense and fully ordered near the substrate, the long molecules arrange themselves in such a way that their tails, facing the vacuum, are well-ordered.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be the result of DNA base interactions with the Al substrate. The growth (or appearance in the case of thymine) of the lower energy peak upon the interaction of various purines and pyrimidines with metals has been reported for thymine on gold, 45 aminopyrimidine on copper 46 and mercaptopurine on gold. 47 Each of the studied sequences has a unique C 1s spectrum, as shown in Fig.…”
Section: X-ray Photoelectron Spectroscopy Of Dna Filmsmentioning
confidence: 96%
“…[2][3][4] The structure and properties of adsorbed nucleobase films deduced from electrochemical studies have been confirmed by several in situ spectroscopy techniques, such as subtractively normalized interfacial Fourier-transform infrared spectroscopy (SNIFTIRS), [5] surface-enhanced infrared reflection-absorption spectroscopy with the attenuated total reflection technique (ATR-SEIRAS), [4,6] surface-enhanced Raman spectroscopy (SERS), [7] surface X-ray scattering (SXS), [8] X-ray photoelectron spectroscopy (XPS), [9] and scanning tunnelling microscopy (STM). [9][10][11][12] These techniques, however, were mostly used to obtain information on monolayer films adsorbed on smooth basal planes or single-crystal surfaces with a low density of monotamic steps and hence reduced surface atomic corrugation. Although the macroscopic information that can be obtained by electrochemical techniques may not reflect the entire complexity of interfacial phenomena, it has long been used to assess the average systematic effect of surface atomic structure details such as regular monoatomic steps and kinks on, for example, the ionic and organic adsorption, electrocatalysis, under-potential deposition and two-dimensional film condensation.…”
mentioning
confidence: 89%